Analgesia preventiva con paracetamol - ibuprofeno por vía oral en pacientes pediátricos sometidos a anestesia general. - Gordillo Valle, María de los Ángeles (2013)
Overview the different schemes of management for postoperative analgesia in the pediatric age group that are used today, demonstrates the absence of controlled clinical studies, to establish a safe and effective therapy. This point is essential, since the implementation of an adequate therapeutic scheme would provide a satisfactory recovery of the patient to be given high early and hassle. The objective was to determine the effectiveness of preventative analgesia, using paracetamol and ibuprofen oral preanesthetic medication in pediatric patients undergoing general anesthesia. This study is descriptive, analytical and prospective, aimed to assess the problem of preventive analgesia in pediatric patients undergoing general anesthesia of the above hospitals. She is predetermine 60 pediatric patients who were chosen at random from among all the children that were valued in the visit preanestesica for undergoing surgery under general anesthesia, which previously 40 minutes before the procedure was les administered ibuprofen and acetaminophen dose that corresponds according to the weight of each patient, 20 children were 8 and 9 years old, 13 children were 10 and 11 years and 27 children of 12 and 13 years, 58% were male and 42% were female. Vital signs remained stable during the transanestésico, which meant that you there was to modify the dose of anesthetic or hypnotic. According to the visual analog scale applied every 15 minutes up to 3 hours in the postoperative was obtained that: 53% of the patients reported mild pain, 40% had moderate pain and 7% severe pain. Conclusions: the previous administration of paracetamol and ibuprofen was moderately effective to control postoperative pain; but this result is not a significant fact that demonstrates that these two drugs are It is effective by itself alone, since it was necessary to add rescue dose to control postoperative pain in children who had moderate and severe pain, the two drugs were safe since no adverse effects were obtained, also that it was not necessary to alter the dosages of anesthetic drugs on the features, which remained hemodynamically stable patient.